Agrotóxicos e a disfunção intestinal: efeitos do fungicida Tebuconazol na homeostase e plasticidade mioentérica de ratos wistar (Rattus Novergicus) - Lopes, Beatriz Soares [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
In recent decades, there has been intense growth in agricultural production and the use of pesticides worldwide. In Brazil, they are the second most sold and consumed class, corresponding to approximately 17.9% and 23%, respectively. TEB is a typical triazole fungicide, well-known with several studies linking it to intestinal alterations and its neurotoxic potential, such as cognitive impairment, neurodegeneration, and changes in the composition and diversity of the gut microbiome. Considering that the route of exposure to the contaminant is oral, the gastrointestinal tract (GIT) acts as an important barrier against harmful substances present in the intestinal lumen. Thus, the GIT is a potential biomarker for understanding the consequences of these contaminants in the organism. Therefore, this study evaluated neuronal alterations in the small intestine of male Wistar rats that received concentrations of 10, 20, and 50 mg/kg of TEB via gavage for 30 consecutive days. After the experimental period, the animals were euthanized, and the duodenum, jejunum, and ileum were collected and subjected to a technique for identifying metabolically active neurons. The results obtained showed a dose-dependent effect of the contaminant, with a significant reduction in neuronal density, more pronounced in the higher dose group in all intestinal segments. Only the ileum also showed a reduction at lower doses. In this sense, we observe the effectiveness of the GIT as a good biomarker, owning several mechanisms to respond to the contaminant.

Nas últimas décadas, houve um crescimento intenso da produção agrícola e do uso de agrotóxicos em todo o mundo. No Brasil, eles constituem a segunda classe mais vendida e consumida, correspondendo a aproximadamente 17,9% e 23%, respectivamente. O TEB é um fungicida típico do grupo dos triazóis, amplamente conhecido, com diversos estudos que o relacionam a alterações intestinais e ao seu potencial neurotóxico, como prejuízo cognitivo, neurodegeneração e mudanças na composição e diversidade da microbiota intestinal. Considerando que a via de exposição ao contaminante é oral, o trato gastrointestinal (TGI) atua como uma importante barreira contra substâncias nocivas presentes no lúmen intestinal. Dessa forma, o TGI é um potencial biomarcador para a compreensão das consequências desses contaminantes no organismo. Assim, este estudo avaliou alterações neuronais no intestino delgado de ratos Wistar machos que receberam concentrações de 10, 20 e 50 mg/kg de TEB por gavagem durante 30 dias consecutivos. Após o período experimental, os animais foram eutanasiados, e o duodeno, jejuno e íleo foram coletados e submetidos a uma técnica para identificação de neurônios metabolicamente ativos. Os resultados obtidos demonstraram um efeito dose-dependente do contaminante, com redução significativa da densidade neuronal, mais pronunciada no grupo que recebeu a maior dose, em todos os segmentos intestinais. Apenas o íleo também apresentou redução nas doses mais baixas. Nesse sentido, observa-se a eficácia do TGI como um bom biomarcador, por possuir diversos mecanismos de resposta ao contaminante.
Pesticides and intestinal dysfunction: effects of the fungicide Tebuconazole on myenteric homeostasis and plasticity in Wistar rats (Rattus norvegicus)
Keywords: Fungicidas; Ratos Wistar; Perda Neuronal; Neurogastroenterologia; Sistema Nervoso Entérico